(untitled) (Research, Society and Development, 2022)
Cannabis Sativa is an herbaceous species of the Cannabaceae genus that exists since primitive times. It can be used as food, fiber source, drug and medicine, being accepted for therapeutic purposes. It has benefits in several pathologies such as: Human Immunodeficiency Virus (HIV); Acquired Immune Deficiency Syndrome (AIDS); Cancer; Glaucoma; Multiple sclerosis; Epilepsy; Algia and Anxiety. Epilepsy is considered a chronic disorder in the brain whose defining characteristics are seizures, neurological and psychiatric consequences. This study aimed to investigate whether nursing students have knowledge about the use of the plant through herbal medicine and in the treatment of epilepsy. This is a cross-sectional, quantitative study, based on investigation fields with an applied nature and exploratory objectives. Aninterview was carried out with (n=77) nursing students with active enrollment at a Faculty in Southwest of Goiás, the analysis of the data was developed using the Microsoft Ofice Excel 2010 program. Thus, the data showed that 66.2% (n=51) claimed to know about the risks and benefits of Cannabis Sativa, and 33.8% (n=26) declare that they have no knowledge about the use of the plant for therapeutic purposes. It is concluded that most of the Nursing students approached do not have knowledge about Cannabis Sativa in the therapeutic treatment used in epilepsy.